Identification of Oil Vertical Migration Through Tectonic Fractures: A New Insight into the Oil Migration Process in the Central Ordos Basin, China - Yiwei Ren; Aiguo Wang; Yanjun Du; Chunyu Li; Bianyang Wang; Zilong Li; Jie Wang; Jinxiang Wei (Energies)
Identifying oil migration through tectonic fractures in stable cratons is always challenging due to limited technical approaches. Here, we provide a case study showing that combined geochemical and geological analyses are a robust tool for identifying oil vertical migration through tectonic fractures. The core samples and crude oils from the Mesozoic petroleum system in the Zhijing area were investigated by an integrated analysis including petrography, biomarkers, nitrogen compounds, and spatial distribution. The tectonic fractures in the Yanchang Formation (YcF) are more developed compared to the Yan’an Formation (YaF), influencing oil migration patterns and reservoir distribution. Eighty-one percent of the tectonic fractures are filled with calcite cement, while only two percent of the tectonic fractures contain solid bitumen. The YaF and YcF oils originating from the same oil source are at the same maturity level. However, the YaF oils exhibit disordered nC18- distribution and “mismatches” at n-undecane and a decrease in toluene/n-heptane ratios, which resulted from the phase fractionation caused by the vertical migration through tectonic fractures. The spatial distributions of 1/4-MC, 1,8/2,7-DMC, and Ts/Tm values in the YaF oils are irregular. Furthermore, the areas occupied by the YaF oil reservoirs exhibit an absence of YcFs, and vice versa. These distribution patterns can be explained by oil vertical migration through tectonic fractures. A series of pieces of evidence indicates that the oils migrated vertically through tectonic fractures to the YaF. This study offers new insights into the oil migration process within the Mesozoic petroleum system of the central Ordos Basin and serves as guidance for identifying oil migration through tectonic fractures in stable cratons.